Urban emissions of water vapor in winter. Issue 17 (4th September 2017) - Salmon, Olivia E.; Shepson, Paul B.; Ren, Xinrong; Marquardt Collow, Allison B.; Miller, Mark A.; Carlton, Annmarie G.; Cambaliza, Maria O. L.; Heimburger, Alexie; Morgan, Kristan L.; Fuentes, Jose D.; Stirm, Brian H.; Grundman, Robert; et al.
Abstract: Elevated water vapor (H2 Ov ) mole fractions were occasionally observed downwind of Indianapolis, IN, and the Washington, D.C.‐Baltimore, MD, area during airborne mass balance experiments conducted during winter months between 2012 and 2015. On days when an urban H2 Ov excess signal was observed, H2 Ov emission estimates range between 1.6 × 10 4 and 1.7 × 10 5  kg s −1 and account for up to 8.4% of the total (background + urban excess) advected flow of atmospheric boundary layer H2 Ov from the urban study sites. Estimates of H2 Ov emissions from combustion sources and electricity generation facility cooling towers are 1–2 orders of magnitude smaller than the urban H2 Ov emission rates estimated from observations. Instances of urban H2 Ov enhancement could be a result of differences in snowmelt and evaporation rates within the urban area, due in part to larger wintertime anthropogenic heat flux and land cover differences, relative to surrounding rural areas. More study is needed to understand why the urban H2 Ov excess signal is observed on some days, and not others. Radiative transfer modeling indicates that the observed urban enhancements in H2 Ov and other greenhouse gas mole fractions contribute only 0.1°C d −1 to the urban heat island at the surface. This integrated warming through the boundary layer is offset by longwave cooling by H2 Ov at the top of the boundary layer. While the radiative impacts of urban H2 Ov emissions do not meaningfully influence urban heat island intensity, urban H2 Ov emissions may have the potential to alter downwind aerosol and cloud properties. Key Points: Unique airborne data reveal elevated H2 Ov mole fractions downwind of urban areas in winter months Estimates of H2 Ov emitted from fossil fuel combustion account for less than 10% of the observed urban H2 Ov enhancement Combustion and evaporative cooling cannot account for the urban H2 Ov excess, leaving enhanced urban evaporation as a plausible explanation